Assessing the Impact of Air Quality on Respiratory Health in Urban Environments: A Case Study of Tangerang - Anurogo, Dito; Sulaeman, Sulaeman; Yamtana, Yamtana; Andarmoyo, Sulistyo (West Science Interdisciplinary Studies, 2023)
This study explores the complex interplay of respiratory health, air quality, and demographic traits in the Tangerang locality. Moderate pollution levels were found through continuous monitoring of air quality measures, such as particulate matter (PM2.5 and PM10), nitrogen dioxide (NO2), sulfur dioxide (SO2), and ozone (O3). A 12% rise in hospital admissions for respiratory illnesses and a prevalence of symptoms were found in respiratory health assessments, which included surveys and health records. Analyses of correlation and regression highlighted the importance of O3, PM2.5, and NO2 in affecting respiratory health outcomes. The insights pertaining to demographics revealed differences in vulnerability among various age groups, genders, and occupational categories. The results inform suggestions for focused interventions, continuous surveillance, public education initiatives, and subcategory evaluations to tackle the complex issues brought about by air pollution in Tangerang.